2014
DOI: 10.1016/j.jviromet.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an infectious cDNA clone of Enterovirus 71: Insights into the factors ensuring experimental success

Abstract: Enterovirus 71 (EV 71) is a causative agent of mild Hand Foot and Mouth Disease but is capable of causing severe complications in the CNS in young children. Reverse genetics technology is currently widely used to study the pathogenesis of the virus. The aim of this work was to determine and evaluate the factors which can contribute to infectivity of EV 71 RNA transcripts in vitro. Two strategies, overlapping RT-PCR and long distance RT-PCR, were employed to obtain the full-length genome cDNA clones of the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In previous studies, infectious clones were successfully developed for a number of enteroviruses with different methods. EV71 or CA16 cDNA clones were established by assembling segmented cDNA fragments of the viral genome into a DNA vector via specific cleavage sites [15, 23, 24], and CA6 or Echo25 cDNA clones were constructed by utilizing In-Fusion Cloning to assemble the full length of viral genome and vector, which was difficult to operate. [16, 19].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, infectious clones were successfully developed for a number of enteroviruses with different methods. EV71 or CA16 cDNA clones were established by assembling segmented cDNA fragments of the viral genome into a DNA vector via specific cleavage sites [15, 23, 24], and CA6 or Echo25 cDNA clones were constructed by utilizing In-Fusion Cloning to assemble the full length of viral genome and vector, which was difficult to operate. [16, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggest that transfection of in vitro synthesized infectious RNA with precise 3’ ends showed no difference in virus titers when compared with infectious RNA with additional non-viral nucleotides at the 3’ end [ 45 , 53 ]. However, our data demonstrated that the presence of a self-cleavage HDV ribozyme sequence at the 3’ end significantly increased overall virus yield of the DNA-launched infectious clone after transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Barring a gross genetic defect, the sampled RNA genomes found in vivo are functional in vitro . Studies of Enterovirus 71 have shown that cloning from half genomes and construction of recombinant genomes versus cloning from full-length PCR amplicons led to less functional clones from the same virus stock which again suggests that laboratory-induced recombination is detrimental to virus integrity [25]. Although viruses such as HIV-1 can often generate recombinants in vivo , these likely emerge only after in vivo selection for replication competent viruses and that in the absence of this selection in vitro, constructed chimeras will more likely produce defective genomes.…”
Section: Discussionmentioning
confidence: 99%